History, theology, and narrative rhetoric in the Fourth Gospel - Attridge, Harold W. (The Pere Marquette theology lecture, 2019)
"The Gospel of John, one of the most enigmatic writings of the early Christian movement, has continued to produce sophisticated scholarly analyses of its literary form, its relationship to the Jesus of history, and its fundamental theological claims. Drawing on contemporary Johannine scholarship this study explores how the gospel weaves into a dramatic narrative a process of serious reflection on a fundamental question of religious epistemology, how one can possibly come to a knowledge of a mysterious God through a special human witness"--